2014
DOI: 10.1111/ijlh.12261
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis affects most routine and cell population data (CPD) obtained using the Sysmex XN‐2000 blood cell analyzer: neutrophil‐related CPD NESFL and NEWY provide useful information for detecting sepsis

Abstract: Sepsis patients demonstrated significant changes in routine and CPD items related to RBC, neutrophils, lymphocytes, and platelets when compared to NCs. Increase in CPD items NE-SFL and NE-WY, which may indicate neutrophil immaturity or activation, could be useful for the detection of sepsis patients, in conjunction with currently used surrogate sepsis biomarkers. However, these items did not efficiently contribute to the discrimination of sepsis severity or predict mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
56
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 12 publications
6
56
2
Order By: Relevance
“…Indeed, the diagnostic performance measured in the present study was lower than that reported by Ansari-Lari and others, (8,17) and this is clearly attributable to the fact that we used a more suitable control population (i.e., ICU patients) rather than a group of healthy controls. Unlike in our study, moreover, Ansari-Lari did not use the validated criteria of the International Sepsis Definition Conference (4) for diagnosing sepsis.…”
Section: Discussioncontrasting
confidence: 87%
“…Indeed, the diagnostic performance measured in the present study was lower than that reported by Ansari-Lari and others, (8,17) and this is clearly attributable to the fact that we used a more suitable control population (i.e., ICU patients) rather than a group of healthy controls. Unlike in our study, moreover, Ansari-Lari did not use the validated criteria of the International Sepsis Definition Conference (4) for diagnosing sepsis.…”
Section: Discussioncontrasting
confidence: 87%
“…These basically include IG (10,11), or the high fluorescence lymphocyte cells (HFLCs) count, a parameter which is usually related to the presence of activated lymphocytes, plasma cells and other blast cells (12). Additional research parameters characterizing different leukocyte populations [i.e., cell population data (CPD)] such as neutrophils (NE), lymphocytes (LY) and monocytes (MO) have recently became available, and preliminary observations suggest that their assessment may be useful in the diagnosis of myelodysplastic syndromes (13,14) and sepsis (15).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil Reactive Intensity, expressed in fluorescence intensity, is representative of the mean fluorescence of the neutrophils and can therefore be related to the activation or immaturity of the population. It is derived from NEUT-Y on XE instruments and few data are available relating the value of this parameter to infection disease/sepsis management [4,5]. NEUT-WY represents the width of the neutrophil scattergram in the WDF channel on the fluorescence axis.…”
mentioning
confidence: 99%